Conical Tank Level Control with Fractional Pid - Travieso-Torres, J; Travieso-Torres, J (IEEE Computer Society, 2016)
A simulation study of fractional order PID (FOPID) applied to level control in a conic tank is presented in this paper. An improved mathematical model to represent better the nonlinear dynamic of the conic tank is derived first. This new model is then used to design FOPID with tunning parameters optimized using Particle Swarm Optimization (PSO). The results obtained under reference level changes, are compared with those obtained using standard PID controllers with parameters tunned using the Root Locus Method (RLM) and also with PSO. From this comparison it is concluded that PSO tunned controllers present a better behavior as compared with RLM tunned controllers, considering the Integral of the Absolute Error (IAE) index. Among the PSO tunned controllers the FOPI is the one that had the lowest IAE. © 2016 IEEE.